(untitled) (Ocean and Coastal Research, 2022)
Estuaries are important environments for birds as resting and foraging sites. Therefore, information about the abundance, distribution, and biology of bird populations are necessary for preservation of such ecosystems. In this work, we studied the dynamic population of birds at Baixio do Arrozal, Trapandé Bay, Cananéia Estuary on the southern coast of São Paulo state, Brazil. As an original hypothesis, we expected that the species abundances would display differences across months and seasons. Using the point count method, bird data were collected monthly between April and December 2013. For comparing the assemblages, a bar chart of the total abundance as a function of the monthly frequency was used along with boxplot graph of this index as a function of the seasons. We also investigated variations in the abundance of some specific bird populations. The results obtained for the total abundance indicated a seasonal pattern, peaking during the warmer months. The population analyses showed a greater abundance occurring in spring/summer, and a decrease of resident species populations in the winter. Migratory birds were recorded in the autumn and spring, following the migratory movements. This demonstrated that bird assemblages varied according to seasons due to the life cycle and the population sizes. Therefore, Baixio do Arrozal is an important environment for avifauna, which use the area throughout the year and need to be preserved.